Technology-Enhanced Thinking Scaffolding in Musical Education - Banut, Marius; Albulescu, Ion (Journal on efficiency and responsibility in education and science, 2024)
In pedagogical language, “scaffolding” is frequently used to replace the expression “support in learning”. In didactic terms, the practice in the classroom shows that various types of support, such as the teacher, colleagues, and technologies, contribute to more efficient learning. In terms of technologies, the present study aims to test the role of programming as a scaffolding agent in learning music theory by memorizing and understanding musical notation elements. In this sense, a sample of 87 students (N = 87) from an urban environment in Romania carried out programming activities using the Sonic Pi application in the Music and movement classes, implemented through an educational project with 24 lessons designed for integrated music-programming learning. The study results describe the acquisition of knowledge, in terms of recognition of musical notation elements, achieved under the influence of cognitive capacities scaffolded by digital technologies. Better post-test results and homogeneous variances between and within the three classes of the participant's sample confirm the possibility of achieving technology-enhanced thinking scaffolding in musical education. The results of the music-programming integrated learning framework could be translated into a more efficient use of teaching time and an increased flexibility of interactions.